KREATIVITAS SENI GRAFIS LINOCUT DI MASA PANDEMI - Dwi Novita Sari (Jurnal Nawala Visual, 2021)
For some people, limiting activities during the pandemic actually makes them more creative, such as graphic and fine arts artists from Bali who are members of "cukilin" collaborating and cooperating with several parties such as studios, restaurants and coffee shops located in Canggu - Bali, making workshops linocut which includes high printing techniques, through the creative process of drawing sketches, then cuts it to follow the image pattern before finally becoming a stamp as a print reference, which can be used repeatedly on media such as cloth, paper, etc. Of course, this workshop activity follow the regulation of health protocols according to existing standards. Furthermore, in this study refers to the qualitative method based on the results of observations, interviews, documentation and literature study. With the results of research how the creativity of linocut, which is one of the earliest (ancient) techniques with manual processing, was able to attract local and foreign people during a pandemic. Not only does it just release boredom from online activities during the pandemic, this Linocut graphic arts creativity also produces creative products that have value and function. Key words : Creativity, linocut/ lino printmaking, pandemic